Toxin-triggered interleukin-1 receptor signaling enables early life discrimination of pathogenic versus commensal skin bacteria - Leech, John M. (Cell Host Microbe, 2019)
The host must develop tolerance to commensal microbes and protective responses to infectious pathogens, yet the mechanisms enabling a privileged relationship with commensals remain largely unknown. Skin colonization by commensal Staphylococcus epidermidis facilitates immune tolerance preferentially in neonates via induction of antigen-specific regulatory T cells (Tregs). Here we demonstrate that this tolerance is not indiscriminately extended to all bacteria encountered in this early window. Rather, neonatal colonization by Staphylococcus aureus minimally enriches for antigen-specific Tregs and does not prevent skin inflammation upon later life exposure. S. aureus α-toxin contributes to this response by stimulating myeloid cell production of IL-1β, which limits S. aureus-specific Tregs. Loss of α-toxin or the IL-1 receptor increases Treg enrichment, whereas topical application of IL-1β or α-toxin diminishes tolerogenic responses S. epidermidis. Thus, preferential activation of a key alarmin pathway facilitates early discrimination of microbial foe from friend, thereby preventing tolerance to a common skin pathogen.